CONCEPT, REGULATORY FRAMEWORK AND TYPES OF RESTRICTIONS OF RIGHTS OF PEOPLE SENTENCED TO IMPRISONMENT - Pyvovar, Iryna; Pyvovar, Yuriy (Proceedings of National Aviation University, 2018)
Purpose: to develop theoretical and legal basis and analyze regulatory framework of restrictions of rights of people sentenced to imprisonment. Methods: structured system, comparative legal, special juridical and logical-normative methods were methodological foundation of the study. Results: there have been defined features of restrictions of rights of people sentenced to imprisonment on the basis of which the definition of the restriction is given; the legal and regulatory framework for restricting the rights of prisoners is systematized. There is defined the absence of clear system and continuity in restrictive norms in the scheme of “international legal norms – constitutional norms – norms of special criminal executive legislation”. The paper makes the case for establishing restrictions of rights of people sentenced to imprisonment exclusively by law. The rational criteria for the classification of restrictions of rights are determined, as well as the characteristics of restrictions of rights of convicts are formulated. Discussion: the defined definition, essential features of restriction of rights of people sentenced to imprisonment, the systematization of normative legal sources regulating such restrictions, as well as the classification of the types of rights restrictions of the specified category of people are proposed to be used as theoretical basis for further scientific research of the issues of securing rights and freedoms of people sentenced to imprisonment.